Implementation of the ROC and CPI Methods for New Employee Selection at PT. Neora Infrastructure Indonesia - Roza, Yuda Fakhri; Triase, Triase (Sistemasi: Jurnal Sistem Informasi, 2024)
PT. Neora Infrastructure Indonesia is an industrial company engaged in telecommunications and/or telephone transmission network construction services, collaborating with Fiberstar. This necessitates the company to constantly require competent human resources. However, the company must compete with others to acquire competent personnel. Nevertheless, the employee selection process at PT. Neora Infrastructure Indonesia is still manual and takes 2 - 4 weeks, making it difficult for the company to compete in acquiring competent personnel. Therefore, it was decided to develop a decision support system to assist the company in efficiently and effectively selecting employees. The decision support system for employee selection uses the ROC and CPI methods. The ROC method is used to determine the criteria weight values, while the CPI method is used for ranking all alternatives. Quantitative method is the research method used, and several types of UML diagrams including Activity diagram, Class diagram, and Use case diagram are utilized for system design. The RAD method is employed for system development. With the establishment of the decision support system for employee selection using the ROC and CPI methods, it is expected that the company can compete with others in obtaining competent human resources and that the employee selection process becomes efficient and effective